2022
DOI: 10.1021/acs.langmuir.2c02087
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Characteristic and High-Throughput Synthesis of Cadmium Sulfide Nanoparticles with Cubic Hexagonal Phase Junctions in a Chaotic Millireactor

Abstract: A four-stage oscillating feedback millireactor with splitters (S-OFM) was designed to improve the mixing performance based on chaotic advection. Three-dimensional CFD simulations were used to investigate its flow characteristics and mixing performance, and the generation mechanisms of secondary flows were examined. The results show that the mixing index (MI cup ) increased with the increase in the Reynolds number (Re), and MI cup could reach 99.8% at Re = 663. Poincarémapping and Kolmogorov entropy were adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The structure and dimensions of the three OFMs are illustrated in Figure 1, which presents a similar structure to our previous paper. 39,40 The inlet width and feedback channel width are 0.2 and 0.4 mm, respectively. Each of the three OFMs contains a Y-typed inlet, a diverging mixing chamber, and two feedback channels.…”
Section: Oscillating Feedback Microreactormentioning
confidence: 99%
See 2 more Smart Citations
“…The structure and dimensions of the three OFMs are illustrated in Figure 1, which presents a similar structure to our previous paper. 39,40 The inlet width and feedback channel width are 0.2 and 0.4 mm, respectively. Each of the three OFMs contains a Y-typed inlet, a diverging mixing chamber, and two feedback channels.…”
Section: Oscillating Feedback Microreactormentioning
confidence: 99%
“…In contrast to the ordered microreactors, it was disclosed that oscillating feedback microreactors (OFMs) based on chaotic advection can operate at high Reynolds numbers (i.e., high throughput, at Reynolds numbers of 10 2 –10 3 ), which is much larger than those of the ordered lamination flow and segmented flow microreactors (i.e., at Reynolds numbers of 10 –1 –10 2 ) . In addition, the three unique secondary flows (i.e., vortex, feedback, oscillation) can effectively induce chaotic advection, causing the fluids to stretch, fold, and compress, significantly shortening the molecule diffusion distance and improving fluid mixing and mass/heat transfer. Hence, homogeneous concentration and temperature fields could be achieved in OFMs for preparing high-quality nanoparticles with a narrow PSD at high throughput. Lately, we demonstrated that OFMs could be applied for high-throughput production of inorganic nanoparticles, where small samples with narrow PSD could be effectively prepared.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parallel design can increase the throughput linearly to a certain level. 14,15 However, increasing the number of complicated microchannels significantly increases machining and working costs. 16 And it is very difficult to keep the fluids flowing uniformly through each microreactor all the time.…”
Section: Introductionmentioning
confidence: 99%